NIST cybersecurity framework : a pocket guide - Calder, Alan, 1957- (IT Governance Publishing, 2018)
The NIST CSF is a framework for organizations to manage and mitigate cybersecurity risk based on existing standards, guidelines, and practices.
Keywords: National Institute of Standards and Technology (U.S.); Computer security.; Cyberterrorism -- Prevention.; elektronické knihy; electronic books